The anatomy and evolution of industries : technological change and industrial dynamics - Marsili, Orietta, 1966- (Cheltenham : Edward Elgar, 2001)
This book examines the relationship between industrial dynamics and technological change. By combining formal evolutionary modelling with empirical evidence, the book illustrates how the characteristics of innovative processes in different technological regimes influence market structure and dynamics.
Includes bibliographical references and index.
lje 28/01/14
Loans
Keywords: Technological innovations -- Economic aspects; Industries